Solving an electrically conducting nanofluid over an impermeable stretching cylinder problem with a spectral reproducing kernel method (vol 149, pg 8747, 2024) - Foroutan, M. R.; Hashemi, M. S.; Rezapour, Shahram; İnç, Mustafa; Habibi, F. (Springer, 2024)
[Abstract Not Available]